Comparative Oral Absorption of Curcumin in a Natural Turmeric Matrix with Two Other Curcumin Formulations: An Open‐label Parallel‐arm Study. (13th October 2017) - Gopi, Sreeraj; Jacob, Joby; Varma, Karthik; Jude, Shintu; Amalraj, Augustine; Arundhathy, C.A.; George, Robin; Sreeraj, T.R.; Divya, C.; Kunnumakkara, Ajaikumar B.; Stohs, Sidney J.
Abstract : Curcuminoids are the major bioactive molecules in turmeric, and poor bioavailability deters them from being the major components of many health and wellness applications. This study was conducted to assess the bioavailability of a completely natural turmeric matrix formulation (CNTMF) and compare its bioavailability with two other commercially available formulations, namely, curcumin with volatile oil (volatile oil formulation) and curcumin with phospholipids and cellulose (phospholipid formulation) in healthy human adult male subjects (15 each group) under fasting conditions. Each formulation was administrated orally as a single 500‐mg dose in capsule form, and blood samples were analyzed by liquid chromatography mass spectrometry at various time intervals up to 24 h. The ingestion of the CNTMF was very well absorbed and resulted in a mean curcuminoids plasma C max of 170.14 ng/mL ( T max = 4 h) compared with 47.54 ng/mL and 69.63 ng/mL for the volatile oil ( T max = 3 h) and phospholipid ( T max = 2.25 h) formulations, respectively. The extent of absorption of total curcuminoids in the blood for the CNTMF was 6× greater than volatile oil formulation and 5× greater than phospholipids formulation. The results of this study indicate that curcumin in a natural turmeric matrix exhibited greater bioavailability than the two comparator products. Copyright © 2017 John Wiley & Sons, Ltd.